Resveratrol suppresses insulin-like growth factor I-induced osteoblast migration: attenuation of the p44/p42 MAP kinase pathway. Issue 12 (1st December 2020) - Hioki, Tomoyuki; Kawabata, Tetsu; Sakai, Go; Fujita, Kazuhiko; Kuroyanagi, Gen; Matsushima-Nishiwaki, Rie; Kim, Woo; Otsuka, Takanobu; Iida, Hiroki; Tokuda, Haruhiko; Kozawa, Osamu
ABSTRACT: Resveratrol is a natural polyphenol with beneficial antioxidant properties. It suppresses the migration of osteoblast-like MC3T3-E1 cells induced by epidermal growth factor, via SIRT1-mediated inhibition of SAPK/JNK and Akt. Moreover, insulin-like growth factor-I (IGF-I) stimulates the migration involving the pathways of p44/p42 mitogen-activated protein (MAP) kinase and Akt. Therefore, we investigated the effects of resveratrol on IGF-I-induced cell migration. Resveratrol and SRT1720, an activator of SIRT1, suppressed IGF-I-induced migration. Inauhzin, a SIRT1 inhibitor, significantly rescued the inhibition of IGF-I-induced cell migration by resveratrol. Resveratrol inhibited IGF-I-induced phosphorylation of p44/p42 MAP kinase but not Akt. SRT1720 inhibited IGF-I-induced phosphorylation of p44/p42 MAP kinase. Furthermore, PD98059, p44/p42 MAP kinase inhibitor, alone suppressed IGF-I-induced osteoblast migration, but did not affect the suppressive effect of resveratrol when administered concomitantly. These findings strongly suggest that resveratrol suppresses IGF-I-induced osteoblast migration via SIRT1 activation at least partially by attenuating the p44/p42 MAP kinase pathway. Graphical abstract: uf0001 Schematic illustration of the mechanism underlying the effects of resveratrol on the IGF-I-induced migration of osteoblast-like MC3T3-E1cells.